2021
DOI: 10.1111/joim.13338
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and SARS‐CoV‐2 infections: Susceptibility to infections, ischemic heart disease and thromboembolic events

Abstract: Background Comorbidities including ischemic heart disease (IHD) worsen outcomes after SARS‐CoV‐2 infections. High lipoprotein(a) [Lp(a)] concentrations are a strong risk factor for IHD and possibly for thromboembolic events. We therefore evaluated whether SARS‐CoV‐2 infections modify the risk of high Lp(a) concentrations for IHD or thromboembolic events during the first 8.5 months follow‐up of the pandemic. Method Cohort study using data from the UK Biobank during the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
6
20
0
1
Order By: Relevance
“…In this context, following the hypothesis that PCSK9 may suppress the expression of interferon type I, 14,42 we measured this protein without finding any association with in-hospital mortality. Same conclusions were reached for lipoprotein(a), in line with findings reporting that high lipoprotein(a) concentrations do not increase the susceptibility either to SARS-CoV-2 infections or to thromboembolic events 43 .…”
Section: Discussionsupporting
confidence: 81%
“…In this context, following the hypothesis that PCSK9 may suppress the expression of interferon type I, 14,42 we measured this protein without finding any association with in-hospital mortality. Same conclusions were reached for lipoprotein(a), in line with findings reporting that high lipoprotein(a) concentrations do not increase the susceptibility either to SARS-CoV-2 infections or to thromboembolic events 43 .…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the Lp(a)≥30mg/dl group had significantly higher d-dimer concentration, (median 1001 vs. 1256 μg/l) p = 0.0208, with no difference in other coagulation parameters including fibrinogen, INR, thrombin time, prothrombin time and APTT ( Table 3 ). Also, the incidence of pulmonary embolism was not significantly higher in the COVID-19 patients with elevated Lp(a), which is consistent with previous results obtained by Maio S Di et al [ 18 ]. The prothrombotic properties of Lp(a) have been well confirmed in in vitro studies; however, a previous meta-analysis suggests that the association between elevated Lp(a) and VTE remains questionable [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…First, Lp(a) is an acute phase reactant, and its concentration can be consistently boosted during sustained inflammatory states, like that characterizing severe forms of COVID-19 and other acute conditions. This is in keeping with the findings of Nurmohamed et al [ 6 ], who reported a gradual increase of this lipoprotein during hospital stay, directly correlated with IL-6 variations, as well as with those of Lippi et al, who found similar concentrations between patients with COVID-19 and other acute diseased states [ 7 ]. Then, in all three studies that we could identified based on our digital search, Lp(a) values both at baseline (e.g., presumably genetically determined) or during illness progression (i.e., boosted by COVID-19 related inflammation) were found to have an impact on clinical outcome of SARS-CoV-2 infection.…”
supporting
confidence: 92%
“…Then, in all three studies that we could identified based on our digital search, Lp(a) values both at baseline (e.g., presumably genetically determined) or during illness progression (i.e., boosted by COVID-19 related inflammation) were found to have an impact on clinical outcome of SARS-CoV-2 infection. The most important aspect here concerns the interplay of this lipoprotein with the risk of developing both venous and arterial thrombosis, in that a positive association was found in the studies of Nurmohamed et al [ 5 ] and Di Maio et al [ 6 ] ( Table 1 ).…”
mentioning
confidence: 97%
See 1 more Smart Citation